STUDI KOMPARASI TENTANG NIKAH MUT’AH PERSPEKTIF ULAMA SUNNI DAN SYI’AH - Wagiyem Wagiyem (Fakultas Syariah (Syari'ah Faculty ), 2016)
This study is aimed at revealing, elaborating, and comparing the thought of Sunni scholars (Hanafiyah, Malikiyah, Syafi’iyah, and Hanabillah) on temporary marriage (mut’ah marriage) to Syi’ah scholars. It also compares the laws that Sunni and Syi’ah scholar used as reference for their argument. The study describes the thought of Sunni and Syi’ah scholars on mut’ah marriage. According to the findings of this study, Sunni scholars ban mut’ah marriage; they refer to Surah of Al-Qur’an: An-Nisa’ (4): 24, al-Mu’minun (23): 5-7, and ath-Thalaq (65):1. Besides, they state that there are some hadits and ijma’ that also prohibit mu’tah marriage. Meanwhile, Syi’ah scholars argue, by referring to Surah of An-Nisa, that mut’ah marriage is permitted. Further, they explain that mut’ah marriage was allowed at the early Islamic era, and was accepted either by Qur’an or by prophet PBUH. They say that mut’ah marriage was banned by Umar bin Khatab, and it was only his ijtihad. Keywords: Mut’ah marriage, sunni scholars, syi’ah scholars.